(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Through it, we have achieved a complete understanding and adequate awareness of all aspects of our topic and answers to all questions that may arise about it. We hope that our research has been as you had hoped for it, as in this research we have reviewed the qualities and characteristics of clean energy, as well as the method of using it, where the effects that it produces have been observed. Clean energy and its drawbacks. For example, Babil Governorate contains 3,000 generators in the governorate center along with the districts and districts. To calculate the amount of fuel spent during one year for all governorates, we perform the following calculation: Number of generators in the governorate × Quantity of fuel per kv × Number of kv per generator × Number of months !!!!= in the year × Number of governorates × Price One liter Solar cells convert sunlight directly into electrical energy, taking advantage of the electronic properties of a specific type of material known as semiconductor. Renewable energy can contribute to providing the energy needs of various sectors, which leads to savings in traditional energy consumption, in addition to To avoid the negative effects of fossil fuels on the environment, the study aims to analyze the experience of (Brazil) and the possibility of benefiting from this country’s experience in transitioning towards renewable energy in Iraq and setting a framework for the possibility of its application, as the importance of this study lies in exploiting the most important types of renewable energy available in Iraq to promote development. Economic and social. The results of the study showed that there are several researches and studies conducted on renewable energy in Iraq, but they are within a narrow scope, and the reason for this is that it requires huge sums of money, including experience and advanced technology, and Iraq has not taken any serious steps regarding the use of this energy in producing electricity, similar to the experiences of other countries. . The most important recommendations reached by the study were that Iraq needs to adopt an energy policy that recognizes the importance of private sector participation in sharing responsibility, coordinating efforts between the government and local and foreign investors, and seeking help from local and foreign expertise, and to help develop a plan to advance the reality of renewable energy in Iraq, provided that this is based on The strategic plan is based on basic principles, including spreading environmental awareness among citizens by including environmental issues in education